The effect of caregiver-delivered social-communication interventions on skill generalization and maintenance in ASD. (March 2018) - Hong, Ee Rea; Neely, Leslie; Gerow, Stephanie; Gann, Candace
Highlights: This study presents a meta-analytic review of single-case studies involving caregiver-delivered interventions for people with ASD. This study evaluated the effects of the targeted interventions on the skill generalization and maintenance in people with ASD. This review included 34 studies and Tau-U and non-overlap of pairs were calculated with a total of 67 separate contrasts across seven studies. Results indicate that caregiver-delivered interventions have positive effects on the skill generalization and maintenance in people with ASD. Abstract: Background: Although caregiver-delivered social communication interventions have been considered scientifically proven practices for individuals with autism spectrum disorders, it is not well examined if these types of intervention modes are truly effective in promoting skill generalization and maintenance within those individuals with autism spectrum disorders. Aims: The purpose of this meta-analysis was to evaluate the status of the extant literature regarding the measures on generalization and/or maintenance of effects of caregiver-delivered communication interventions for children with autism spectrum disorders. Methods and procedures: This systematic literature review and meta-analysis evaluated peer-reviewed research regarding the effects of caregiver-implemented interventions on the maintenance and generalization of the social-communication skills for children with autism spectrum disorders. A total of 34 articles were included following a systematic search. Articles were summarized according to the following categories: (a) generalization dimension, (b) generalization assessment design, (c) maintenance assessment design, (d) generalization/maintenance teaching strategy, and (e) latency to maintenance probes. After application of design standards, aggregate Tau-U and non-overlap of pairs effect sizes were calculated with a total of 67 separate contrasts across seven studies. Outcomes and results: Overall, effect size scores ranged from small to large effects across all comparisons. On average, most of the baseline to maintenance and generalization comparisons produced moderate to large effects. Whereas, small to moderate or even deteriorate effects were found in most of the intervention to maintenance and generalization comparisons. Conclusions and implications: The findings in this review suggest that caregiver-delivered social-communication interventions are likely to result in mixed effects on skill generalization and maintenance within children with autism spectrum disorders. Implications for future research and practice are discussed.